Vascularization of Patient-Derived Tumoroid from Non-Small-Cell Lung Cancer and Its Microenvironment - Joseph Seitlinger; Anasse Nounsi; Ysia Idoux-Gillet; Eloy Santos Pujol; Hélène Lê; Erwan Grandgirard; Anne Olland; Véronique Lindner; Cécile Zaupa; Jean-Marc Balloul; Eric Quemeneur; Gilbert Massard; et al. (Biomedicines, 2022)
Patient-derived tumoroid (PDT) has been developed and used for anti-drug screening in the last decade. As compared to other existing drug screening models, a PDT-based in vitro 3D cell culture model could preserve the histological and mutational characteristics of their corresponding tumors and mimic the tumor microenvironment. However, few studies have been carried out to improve the microvascular network connecting the PDT and its surrounding microenvironment, knowing that poor tumor-selective drug transport and delivery is one of the major reasons for both the failure of anti-cancer drug screens and resistance in clinical treatment. In this study, we formed vascularized PDTs in six days using multiple cell types which maintain the histopathological features of the original cancer tissue. Furthermore, our results demonstrated a vascular network connecting PDT and its surrounding microenvironment. This fast and promising PDT model opens new perspectives for personalized medicine: this model could easily be used to test all therapeutic treatments and could be connected with a microfluidic device for more accurate drug screening.